Numerical analysis of impact of fault and weak rock formation on mining-induced deformation of rock slope. Issue 3 (October 2021) - Zhang, C; Amagu, C A; Kodama, J.; Sainoki, A; Ogawa, S; Umeda, C; Fujii, Y; Fukuda, D
Abstract: Geological structures, such as fault, geological discontinuity, and weak rock formation are likely to play a critical role in the stability and behaviour of rock slopes. However, the impact of such geological structures on the mining-induced deformation of rock slopes in an open-pit mine remains unclear. This study takes an open-pit limestone quarry in Japan as an example to discuss the mechanical interaction between specific geological structures. In this quarry, below the mining area is a vertical fault intersecting with a weak rock formation almost parallel to the slope surface. Based on these unique geological structures, numerical simulations are conducted in the framework of discrete element method while considering different geological situations to elucidate the impact of each geological structure. The analysis results show that the vertical fault and weak rock formation significantly impact the deformation of the rock slope during mining progression. In the case of a fault-only model, no slip occurs. However, in the case of the fault and weak rock formation model, as the mining face is crossing the fault, apparent slip occurs along the weak rock formation. In this model, although the vertical fault constrains the sliding of the upper discontinuities at the early stage, the normal stress of the weak rock formation decreases gradually as the mining progresses, and local shear failure occurs at the intersection of the weak rock formation and fault, which leads to the slip. However, rock slope displacement due to the slip gradually decreases and eventually stabilizes as the working face gets away from the vertical fault. This study provides new insight into the deformation mechanism of the rock slope and serves as a reference for future mining and slope prevention work.